2014
DOI: 10.15578/jra.9.1.2014.25-30
|View full text |Cite
|
Sign up to set email alerts
|

Penurunan Keragaman Genetik Pada F-4 Ikan Nila Merah “Cangkringan” Hasil Pemuliaan Dideteksi Dengan Marker Genetik

Abstract: ABSTRAKVariasi genetik ikan nila merah "Cangkringan" hasil pemuliaan dimonitor dengan menggunakan marker d-Loop DNA untuk mengetahui pembawa keragaman genetik yang dihasilkan karena kegiatan seleksi. DNA diekstraksi dari sirip ikan nila generasi 1 (F-0) hingga generasi ke-5 (F-4) dan diamplifikasi daerah d-Loop pada mitokondria menggunakan primer LH 1509 dan FH 1202. Secara statistik tidak terdapat perbedaan genotipe yang nyata antara ke-5 generasi ikan nila yang diuji. Terdapat penurunan variasi genetik dan k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
1
Order By: Relevance
“…The synthetic population was formed by crossing Chitralada, Philippines, NIFI, and Singapore tilapia strains and then the best 10% of the population was taken. The results obtained statistically showed that as a result of the selection process there was a 25% decrease in diversity from F-0 to F-4 [4].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The synthetic population was formed by crossing Chitralada, Philippines, NIFI, and Singapore tilapia strains and then the best 10% of the population was taken. The results obtained statistically showed that as a result of the selection process there was a 25% decrease in diversity from F-0 to F-4 [4].…”
Section: Discussionmentioning
confidence: 98%
“…Genetic inheritance is characterized by slow growth, faster gonadal maturation and high mortality due to weak disease and environmental resistance. Alternatives to overcome this problem can be done by breeding, one of which is hybridization [4] There are four types of tilapia based on origin and/or strain used in this study, including nilasa (Cangkringan), red nifi (Sukabumi), pandu (Janti) and tilapia from Sukamandi. Nilasa (Nila strain satria) is a type of red tilapia as a result of individual selection from the Aquaculture Technology Development Center DIY, Cangkringan, which was introduced in 2012 based on the Decree of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number KEP.47/MEN/2012.…”
Section: Introductionmentioning
confidence: 99%
“…Tilapia became an export commodity in place of red sea bream Chrysophrys major marine fish, favored by the world's consumers because it has an attractive meat color, delicious taste and does not have thorns between muskulars. [5]. The improvement in the quality of tilapia seeds depends largely on the quality of the parent.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The individual selection program is conducted by selecting the best 10% of the population in fish that has reached a measure of consumption in each generation. [5]. Information about the spawning process of fish needs to be obtained to find out the quantity and quality of spawning larvae with different sex ratios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Salah satu upaya yang dapat dilakukan untuk meningkatkan kualitas genetik pada karakter yang diinginkan adalah melalui program pemuliaan dengan metode seleksi. Menurut Nugroho et al (2014), kegiatan seleksi merupakan upa-ya untuk mempersempit atau menurunkan variasi sifat tertentu agar lebih stabil dengan memanfaatkan pengaruh silang dalam. Kegiatan seleksi pada ikan nila merah di Balai Riset Pemuliaan Ikan telah dilakukan dalam rangka pembentukan ikan nila merah toleran salinitas tinggi.…”
Section: _____________________________unclassified